EPIDEMIOLOGICAL PROFILE OF DIABETIC SENIORS REGISTERED IN THE HIPERDIA PROGRAM IN THE STATE OF PIAUÍ, BRASIL - Santos, Gleyson Moura dos; Sousa, Paulo Víctor de Lima; Barros, Nara Vanessa dos Anjos (Journal of Health Care, 2018)
Introduction: Aging is an intrinsic process in the natural course of life in which biological, psychologicaland social changes occur, leaving the individual more vulnerable to disease occurrences. Among the mostprevalent diseases, Diabetes mellitus stands out. The Ministry of Health launched the Hypertension andDiabetes Program (Hiperdia) to monitor the distribution of medications. Objective: To describe theprofile of diabetic elderly people enrolled in the Hiperdia in the state of Piauí, between 2005 and 2012.Methods: A cross-sectional descriptive/retrospective population-based study using secondary data on seniorswith diabetes mellitus recorded in Hiperdia and available on the Datasus website. The variables werecategorized into three groups: 1) characterization of the elderly: sex and age; 2) complications: cerebrovascularaccident, acute myocardial infarction, other cardiopathies, renal disease, diabetic foot and diabetesamputation; 3) risk factors: smoking, being overweight and sedentary. Results: Higher prevalence ofelderly with diabetes mellitus type 2 (76.1%). The presence of diabetes mellitus 1 and 2 was predominantin female elderly (61.9% and 61.2%, respectively) in the age group from 60 to 74 years. In 2007, therewere more cases of diabetes mellitus in female seniors, while in 2009 the highest prevalence was in elderlymale. The statistical difference was more significant for the variables diabetes amputation, overweight andobesity. Conclusion: Higher prevalence of elderly people with diabetes mellitus 2, mainly in the femalepopulation, emphasizing the presence of overweight and sedentary lifestyle as the main risk factors.
Keywords: elderly; diabetes mellitus; chronic disease; epidemiology; public health